(1254) A social accounting matrix for Egypt مصفوفة المحاسبة الاجتماعية لمصر - Osman, Osman M. (The Institute Of National Planning., 2018)
Data preparation and organization has always been recognized as a necessary prerequisite for development planning. Both literature and practice point out that for purposes, a social accounting matrix provides a useful vehicle for organizing the data.